Caustic ingestion: development and validation of a prognostic score - Tosca, Joan; Villagrasa, Rosana; Sanahuja, Ana; Sanchez, Ana; Trejo, Galo Antonio; Herreros, Belen; Pascual, Isabel; Mas, Pilar; Peña, Andres; Minguez, Miguel (Endoscopy, 2021)
Background Caustic ingestion is a potentially severe condition and early identification of poor outcome is essential to improve management; however, prediction based on endoscopy alone can overestimate severity. This study aimed to develop and validate a prognostic score.Methods A prospective cohort study was designed to include all consecutive patients aged > 15 years who presented with caustic ingestion between 1995 and 2017. Adverse outcome was defined by intensive care unit admission, urgent surgery, or death. The predictive value of clinical, analytical, and endoscopic variables was assessed in the first cohort (derivation cohort) and a prognostic score based on the resulting risk factors was developed by logistic regression. Internal validation (bootstrapping) was performed and then external validation was checked in an independent sample of patients (validation cohort).Results 469 cases of caustic ingestion were included, 265 in the derivation cohort and 204 in the validation cohort. Ingestion of acidic substances (odds ratio [OR] 3.13, 95 % confidence interval [CI] 2.33 – 4.21), neutrophil count (OR 1.05, 95 %CI 1.04 – 1.06), metabolic acidosis (bicarbonate value, OR 0.82, 95 %CI 0.78 – 0.85), and endoscopic injury (OR 3.81, 95 %CI 3.35 – 4.34) were independent risk factors for poor outcome. The prognostic score based on these variables provided better accuracy than endoscopy alone (P = 0.04), with high sensitivity, specificity, positive and negative predictive values (93.3 %, 92.7 %, 72.7 %, 98.5 %, respectively), and area under the curve (0.976, 95 %CI 0.973 – 0.979; P < 0.001).Conclusions This score allowed a reliable prognosis of caustic ingestion and was more accurate than endoscopy-based evaluation.